2007
DOI: 10.1002/jat.1258
|View full text |Cite
|
Sign up to set email alerts
|

Delayed behavioral and endocrine effects of sarin and stress exposure in mice

Abstract: The organophosphorus agent sarin is a potent inhibitor of acetylcholinesterase. Experiments tested the influence of exposure to low doses of sarin along with psychological stress on delayed behavioral and endocrine changes in mice. Motor activity, acoustic startle response (ASR), pre-pulse inhibition (PPI) of ASR, activity of cholinesterase in blood and catecholamine levels in adrenals were evaluated after low dose sarin exposure (3 x 0.4 LD50 subcutaneously) combined with chronic intermittent stress in C57BL/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Additional surveys have been done using animal models and have focused on exposure to chemical agents used in theatre; namely organophosphates and acetylcholine esterase (AChE) inhibitors such as pyridostigmine bromide (PB) (Golomb, 2008;Amourette et al, 2009) and sarin (Shewale et al, 2012;Mach et al, 2008). Though much of this has focused on proteomic and phospho-proteomic profiling (Torres-Altoro et al, 2011;Zhu et al, 2010), recent work by Barbier et al (2009) surveyed the expression of genes associated with stress response, learning and memory in the hippocampus and hypothalamus of mice.…”
Section: Introductionmentioning
confidence: 99%
“…Additional surveys have been done using animal models and have focused on exposure to chemical agents used in theatre; namely organophosphates and acetylcholine esterase (AChE) inhibitors such as pyridostigmine bromide (PB) (Golomb, 2008;Amourette et al, 2009) and sarin (Shewale et al, 2012;Mach et al, 2008). Though much of this has focused on proteomic and phospho-proteomic profiling (Torres-Altoro et al, 2011;Zhu et al, 2010), recent work by Barbier et al (2009) surveyed the expression of genes associated with stress response, learning and memory in the hippocampus and hypothalamus of mice.…”
Section: Introductionmentioning
confidence: 99%
“…Mach et al (2008) found that exposure of mice to sarin and stress produced delayed endocrine effects as evidenced by the significantly enlarged adrenal glands and the significantly lowered concentrations of NE, epinephrine, DA, and other catecholamine. It is thought that combined exposure to sarin and stress can alter the neural pathways to the adrenal glands and inhibit AChE (Mach et al 2008). …”
Section: Organophosphates-induced Endocrine Disruption (Opied)mentioning
confidence: 96%
“…Delayed behavioral and endocrine effects were studied following subcutaneous exposure to sarin (3 × 0.4 LD 50 ) combined with intermittent shaker stress in C57BL/6J mice (Mach et al 2008). This combination caused delayed behavioral change manifested as excessive grooming and endocrine alterations in adrenal glands seven weeks after sarin exposure.…”
Section: Organophosphates-induced Endocrine Disruption (Opied)mentioning
confidence: 99%
“…[88][89][90][91][92][93][94] OPs can produce several neurotoxic effects depending on the dose, frequency of exposure, type of OP and the host factors that influence susceptibility and sensitivity. In terms of the dose, it is considered low dose when no clinical manifestation is observed and/or the serum cholinesterase level, as biomarker, is at more than 50% of its normal value; a medium dose is achieved when some clinical manifestations are observed like fatigue, headache, dizziness, numbness of extremities, nausea and vomiting, and the serum cholinesterase levels are between 20 and 50% of the normal value (mid) or between 10 and 20% of normal value (severe); high levels of exposure trigger severe clinical manifestations like marked miosis and loss of pupillary reflex to light, muscle fasciculation, flaccid paralysis, pulmonary rales, respiratory distress, cyanosis and unconsciousness.…”
Section: Neurotoxicity Of Opsmentioning
confidence: 99%